Tailoring Bi to boost CuAgBi2I8 solar cells - Erchuang Fan; Manying Liu; Yange Zhang; Dandan Zhao; Yan Lei; Chaoliang Zhao; Peng Zhang; Erjun Zhou; Zhi Zheng (InfoMat)
Abstract Considering sustainable development factors such as element abundance, cost, environmental friendliness, and stability, the research and development of novel inorganic non‐lead perovskites are very significant. Copper‐silver‐bismuth iodide (CABI) is a promising solar cell material with halide perovskite genes, possessing eco‐friendly, element‐rich, and cost‐effective characteristics. The fabrication of high‐quality CABI films with tailored compositions still poses a substantial hurdle. We developed a CuAgBi2I8 material that effectively reduced the bandgap to 1.69 eV by optimizing Bi distribution to create an environment conducive to in‐situ redox reactions of Bi with I2, Cu, and Ag via vapor‐phase synthesis. This strategy proved highly effective in synthesizing high‐quality CuAgBi2I8 compound, accompanied by significant improvements in film quality, including enhanced crystallinity, minimized defects, and reduced non‐radiative recombination. The crystal structure of CuAgBi2I8 and mechanisms of elemental reactions and diffusion are discussed. Devices featuring the structure FTO/c‐TiO2/m‐TiO2/CuAgBi2I8/CuI/Spiro‐OMeTAD/carbon achieved a champion efficiency of 3.21%, the highest for CABI solar cells. This work provides a novel idea and approach to governing the gas–solid element diffusion and reaction for high‐quality CABI and related halide perovskite films.